The Influence of Biofilms on Carbapenem Susceptibility and Patient Outcome in Device Associated K. pneumoniae Infections: Insights Into Phenotype vs Genome-Wide Analysis and Correlation - Devanga Ragupathi, Naveen Kumar; Muthuirulandi Sethuvel, Dhiviya Prabaa; Triplicane Dwarakanathan, Hariharan; Murugan, Dhivya; Umashankar, Yamini; Monk, Peter N.; Karunakaran, Esther; Veeraraghavan, Balaji (Frontiers in Microbiology, 2020)
Klebsiella pneumoniae is one of the leading causes of nosocomial infections. Carbapenem-resistant K. pneumoniae are on the rise globally. The biofilm forming ability of K. pneumoniae further complicates patient management. There is still a knowledge gap on the association of biofilm formation with patient outcome and carbapenem susceptibility, which is investigated in present study. K. pneumoniae isolates from patients admitted in critical care units with catheters and ventilators were included. K. pneumoniae (n = 72) were subjected to 96-well plate biofilm formation assay followed by MBEC assay for subset of strong biofilm formers. Whole genome sequencing and a core genome phylogenetic analysis in comparison with global isolates were performed. Phenotypic analyses showed a positive correlation between biofilm formation and carbapenem resistance. Planktonic cells observed to be susceptible in vitro exhibited higher MICs in biofilm structure, hence MICs cannot be extrapolated for treatment. The biofilm forming ability had a significant association with morbidity/mortality. Infections by stronger biofilm forming pathogens significantly (p<0.05) resulted in fewer ‘average days alive’ for the patient (3.33 days) in comparison to those negative for biofilms (11.33 days). Phylogenetic analysis including global isolates revealed clear association of sequence types with genes for biofilm formation and carbapenem resistance. Known hypervirulent clone-ST23 with wcaG, magA, rmpA, rmpA2 and wzc with lack of mutation for hyper-capsulation might be poor biofilm formers. ST15, ST16, ST307 and ST258 (reported global high-risk clones) were wcaJ negative indicating the high potential of biofilm forming capacity. Genes wabG and treC for CPS, bcsA and pgaC for adhesins, luxS for quorum sensing were common in all clades in addition to genes for aerobactin (iutA), allantoin (allS), type I and III fimbriae (fimA, fimH, mrkD) and pili (pilQ, ecpA). This study is the first of its kind to compare genetic features of antimicrobial resistance with a spectrum covering most of the genetic factors for K. pneumoniae biofilm. These results highlight the importance of biofilm screening to effectively manage nosocomial infections by K. pneumoniae. Further, data obtained on epidemiology and associations of biofilm and resistance genetic factors will serve to enhance our understanding on biofilm mechanisms in K. pneumoniae.